Rasicm And Gender Bias In Entreprenership : Impact On Business Growth And Opportunities In MSMEs - R Suryasaputra; S Syah (International Journal of Social Science and Humanity, 2025)
Racism and gender bias are two major barriers affecting the growth and business opportunities for entrepreneurs in the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. Despite the significant contribution of MSMEs to Indonesia’s economy, women entrepreneurs and those from minority ethnic groups often face challenges in accessing financing, business networks, and broader markets. This article examines the direct and indirect impacts of racial discrimination and gender bias on MSME entrepreneurs, while identifying strategies that can be implemented to create a more inclusive and equitable entrepreneurial ecosystem. Through a literature review and secondary data analysis, this study finds that women entrepreneurs in Indonesia access only 10% of the total loans given to MSMEs, while male entrepreneurs access over 70%. It is recommended that government policies strengthen support for women and minority entrepreneurs through more inclusive financing policies, as well as providing more open mentorship programs and business networks for marginalized groups. By reducing racial discrimination and gender bias, it is hoped that the MSME sector can grow more evenly and sustainably, thereby enhancing Indonesia’s economic competitiveness